(untitled) (Journal of Philosophy Culture and Political Science, 2015)
This article considers globalization as a process, gives some definitions and also investigates impacts of globalization on the values of young people. Globalization is generally defined as the process of global economic, political and cultural integration. Globalization involves the standardization of economic and technological processes and convergence (merger, assimilation) cultures of different countries. Country cannot build a democratic society which is a cost-effective, self-respecting tradition of the people who compose it, without the interested young people’s attitudes. A study of young people is always related to the search key to understanding the future. Youth deeper than all other age groups picks «zeitgeist», stung and accurately distinguishes it authenticity and falsehood.